Tough and conductive hydrotalcite / nanocellulose / PVA (polyvinyl alcohol) composite hydrogel constructed based on Hofmeister effect as well as preparation method and application of tough and conductive hydrotalcite / nanocellulose / PVA composite hydrogel

By adding hydrotalcite and nanocellulose to PVA hydrogels and using frozen salting method, the composite hydrogels were constructed using the Hofmeister effect, the problem of insufficient mechanical properties and conductivity of PVA hydrogels was solved, and materials with high strength, high conductivity and wide temperature adaptability were achieved.

CN119529320APending Publication Date: 2025-02-28JIANGSU UNIV OF TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411715648.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing PVA hydrogels have shortcomings in mechanical properties and electrical conductivity, and it is difficult to meet the requirements of flexible electronic materials.

Method used

By adding hydrotalcite nanosheets and nanocellulose to the PVA solution and using frozen salting method, a strong and conductive hydrotalcite/nanocellulose/PVA composite hydrogel was constructed using the Hofmeister effect.

Benefits of technology

The tensile strength and elongation of PVA hydrogels are significantly improved, and the conductivity is increased by 6.4 times, achieving high strength, high conductivity and a wide temperature application range of PVA composite hydrogel materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529320A_ABST
    Figure CN119529320A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to tough and conductive hydrotalcite / nanocellulose / PVA (polyvinyl alcohol) composite hydrogel constructed based on a Hofmester effect as well as a preparation method and application thereof, and belongs to the technical field of preparation of high polymer materials. The preparation method of the tough and conductive hydrotalcite / nanocellulose / PVA composite hydrogel constructed on the basis of the Hofmean effect comprises the following steps: mixing hydrotalcite nanosheets, nanocellulose dispersoid and a PVA solution, stirring and carrying out ultrasonic treatment to obtain a composite mixture; and carrying out freezing salting-out treatment on the composite mixture to obtain the hydrotalcite / nanocellulose / PVA composite hydrogel. According to the invention, LDH nanosheets and nanocellulose are added as reinforcing agents, and a freezing salting-out method is used, so that the PVA-based conductive ion hydrogel with firm mechanical properties and enhanced conductivity is constructed; and an internal hydrogen bond network in the hydrogel matrix is formed by freezing and Hofmester effect, so that the composite hydrogel with a hierarchical porous structure is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the technical field of polymer material preparation, and in particular to a tough and conductive hydrotalcite / nanocellulose / PVA composite hydrogel constructed based on the Hofmeister effect, and a preparation method and application thereof. Background Art

[0002] Hydrogel is a material with water as dispersion medium and a three-dimensional network structure, which has great application potential in biology, medicine and flexible electronic materials. According to the source of its raw materials, hydrogels can be divided into two categories: natural and synthetic. Traditional natural hydrogels, such as collagen and gelatin, have ideal biocompatibility and biodegradability. However, they are often accompanied by higher costs and relatively poor mechanical properties. Polyvinyl alcohol (PVA) is a typical synthetic polymer that can be precisely controlled by chemical synthesis to obtain PVA hydrogel materials with specified structures and properties. However, PVA hydrogel materials usually exhibit defects in related applications, including insufficient mechanical strength, insufficient biocompatibility, low signal transmission efficiency and limited environmental adaptability.

[0003] The method of developing functional materials based on PVA hydrogel needs to start from the perspective of practical needs and construct PVA composite hydrogel materials by introducing functional or auxiliary components. In order to meet the specific requirements of PVA hydrogel materials in the fields of biomedicine, tissue engineering and drug controlled release, related research including composite hydrogel materials such as PVA / gellan gum, PVA / chitosan and PVA / hydroxyapatite has been studied in depth. The main obstacle to applying PVA ion hydrogels to flexible electronic materials is their mechanical properties and conductivity.

[0004] The preparation routes of PVA hydrogel mainly include chemical crosslinking and physical crosslinking. Since the residual chemical crosslinkers in crosslinked PVA hydrogels may pose potential risks to health, physically crosslinked PVA hydrogels are more suitable for flexible sensing devices with higher biocompatibility requirements. At present, the main method for physically crosslinking PVA hydrogels is repeated freezing and thawing. During the freeze-thaw cycle, the dissolved PVA molecules undergo phase separation and crystallization and are converted into hydrogels. However, the mechanical properties of PVA hydrogels directly prepared by repeated freezing and thawing are relatively low, with tensile strength and tensile modulus of only 0.5MPa and 0.76MPa. By adding inorganic nanoparticles such as bentonite, montmorillonite, laponite and graphene, the mechanical properties of PVA composite hydrogels can be significantly improved, making PVA hydrogels show higher elasticity and rigidity.

[0005] Layered double hydroxides (LDH), also known as hydrotalcites, constitute a class of inorganic functional materials characterized by their unique structure, including positively charged metal hydroxide layers and exchangeable anions dispersed in the interlayer region. Specifically, LDH nanosheets are mainly used as reinforcing agents in hydrogel materials, which are beneficial to improve their mechanical properties and optimize the hydrogel structure. At the same time, the research on the preparation of PVA composite hydrogels using nanocellulose as a reinforcing agent has also attracted increasing attention. Nanocellulose has excellent mechanical strength, high chemical resistance and good biocompatibility. It is an ideal candidate for use as a substrate, adhesive and hydrogel electrolyte in flexible electronic devices. Based on the high specific surface area and abundant hydroxyl groups of nanocellulose, it can form dense hydrogen bonds with PVA molecules during the freeze-thaw process, and evenly distribute the cross-linking points of the three-dimensional network structure, reduce the pore size, and thus improve the mechanical properties of the composite gel. At the same time, the addition of nanocellulose can promote the crystallization of PVA molecules. However, although the addition of reinforcing agents can significantly improve the mechanical strength of PVA hydrogels, their mechanical properties are not sufficient to meet the requirements of flexible ion gel materials.

[0006] In recent years, freeze-assisted salting-out treatment has been used to prepare PVA hydrogels. Based on directional freeze-forming and the Hofmeister effect, PVA hydrogels have multi-level anisotropic structures at different scales from molecules to millimeters, which significantly improves the strength, toughness and fatigue resistance of PVA hydrogels. According to the Hofmeister effect, different salt ions can induce different degrees of aggregation of PVA molecular chains, thereby achieving large-scale regulation of the mechanical properties of hydrogels. Subsequently, the Hofmeister effect was further applied to the preparation of physically cross-linked strong and tough PVA composite hydrogels, which showed good application prospects in underwater sensors, gel ionization sensors and hydrophilic sponge materials.

[0007] Conductive hydrogel is one of the basic materials for building flexible sensors, and polyvinyl alcohol (PVA) is a commonly used material for hydrogel. However, current PVA hydrogels have obvious defects in strength and conductivity. Summary of the invention

[0008] In view of this, the embodiments of the present application provide a strong and conductive hydrotalcite / nanocellulose / PVA composite hydrogel constructed based on the Hofmeister effect, and a preparation method and application thereof. By adding LDH nanosheets and nanocellulose as reinforcing agents and using the freezing salting-out method, a PVA-based conductive ion hydrogel with strong mechanical properties and enhanced conductivity is constructed; freezing and the Hofmeister effect will form an internal hydrogen bond network within the hydrogel matrix, thereby preparing a composite hydrogel with a hierarchical porous structure, which can effectively overcome the defects of the above-mentioned prior art.

[0009] The first aspect of the embodiment of the present application provides a method for preparing a strong and conductive hydrotalcite / nanocellulose / PVA composite hydrogel based on the Hofmeister effect, comprising the following steps:

[0010] The hydrotalcite nanosheets, nanocellulose dispersion and PVA solution are mixed, stirred and subjected to ultrasonic treatment to obtain a composite mixture; the composite mixture is subjected to freeze-salting-out treatment to obtain a hydrotalcite / nanocellulose / PVA composite hydrogel.

[0011] The freezing and salting-out process based on the Hofmeister effect can effectively improve the strength of PVA. This application uses hydrotalcite and nanocellulose as additives and adopts the freezing and salting-out method to construct PVA composite hydrogel. Due to the reconstruction of hydrogen bonds and the construction of a multilayer three-dimensional network structure, the tensile strength and elongation of the PVA composite hydrogel are increased to 8.2 times and 8.1 times that of pure PVA hydrogel, respectively. At the same time, with the significant increase in ion content and the effective establishment of a transmission path, the conductivity of the PVA composite hydrogel is increased by 6.4 times. Based on the characteristics of high ion concentration and stable network structure, the composite hydrogel exhibits excellent elasticity and strain recovery properties in the range from low temperature to room temperature. This work realizes the construction of PVA composite hydrogel materials with high strength, high conductivity and a wide temperature application range, which provides new ideas for the development of flexible biosafety sensors.

[0012] In some embodiments that may include the above embodiments, the specific process of freezing salting out is:

[0013] The frozen hydrotalcite / nanocellulose / PVA composite hydrogel was immersed in a Na2SO4 solution with a concentration of 0.5-2.0 M for salting out for 6-36 hours to promote shape formation.

[0014] In some embodiments, which may include the above embodiments, the preparation process of the nanocellulose dispersion is:

[0015] NaBr and TEMPO were dissolved in deionized water, and then cellulose pulp was added. NaClO solution was gradually added dropwise to the mixture to start oxidation. During the oxidation process, the pH value of the mixture was continuously monitored and maintained at 9.8-11.5 by adding NaOH solution dropwise. When the pH value of the mixture decreased by less than 0.05 per hour, ethanol was added to quench the oxidation. The pH of the mixture was adjusted to neutral by adding HCl solution. Centrifugation was repeated at 10000 rpm for 6 minutes. The precipitate was washed with distilled water to obtain oxidized cellulose. The oxidized cellulose was then dispersed in distilled water to 0.2 wt %, and ultrasonically treated at a power of 1300 w for 10 minutes and stored in a refrigerator for use.

[0016] In some embodiments, which may include the above embodiments, the ratio of NaBr, TEMPO, deionized water, cellulose pulp and NaClO is 0.4 g: 0.064 g: 400 mL: 4 g: 10 mL.

[0017] In some embodiments, which may include the above embodiments, the concentration of the NaOH solution is 0.5M and the concentration of the HCl solution is 0.5M.

[0018] Specifically, the preparation process of nanocellulose dispersion is:

[0019] 0.4 g NaBr and 0.064 g TEMPO were dissolved in 400 mL deionized water, followed by the addition of 4 g cellulose pulp, and 10 mL of a 24 mmol NaClO solution was gradually added dropwise to the mixture to start oxidation. During the oxidation process, the pH of the mixture was continuously monitored and maintained at 9.8-11.5 by the dropwise addition of a 0.5 M NaOH solution. When the pH of the mixture decreased by less than 0.05 per hour, 2 mL of ethanol was added to quench the oxidation. The pH of the mixture was adjusted to neutral by the addition of a 0.5 M HCl solution, and the centrifugation was repeated at 10,000 rpm for 6 minutes. The precipitate was washed with distilled water to obtain oxidized cellulose, and then the oxidized cellulose was dispersed in distilled water to 0.2 wt %, and ultrasonically treated at a power of 1300 w for 10 minutes and stored in a refrigerator for use.

[0020] In some embodiments that may include the above embodiments, the preparation process of the hydrotalcite nanosheets is:

[0021] The hydrotalcite aqueous solution was ultrasonically treated at a power of 1300 W for 20 minutes to obtain hydrotalcite nanosheets.

[0022] In some embodiments that may include the above embodiments, the preparation process of the PVA solution is:

[0023] PVA solution was prepared by dissolving PVA in water at 100°C.

[0024] In some embodiments, which may include the above embodiments, the concentrations of nanocellulose, hydrotalcite and PVA in the hydrotalcite / nanocellulose / PVA composite hydrogel are 0.6-1.2 wt%, 1.2 wt% and 8 wt%, respectively.

[0025] The second aspect of the embodiments of the present application also provides a strong and conductive hydrotalcite / nanocellulose / PVA composite hydrogel based on the Hofmeister effect prepared according to the above-mentioned preparation method.

[0026] The third aspect of the embodiments of the present application also provides the use of the tough and conductive hydrotalcite / nanocellulose / PVA composite hydrogel constructed based on the Hofmeister effect in the preparation of a flexible strain sensor.

[0027] Compared with the prior art, the embodiments of the present application have the following beneficial effects:

[0028] 1. The present application discloses an effective method for preparing tough PVA-based conductive ion hydrogels. By incorporating LDH nanosheets and nanocellulose into PVA solution and applying a freezing salting-out process, the mechanical properties and electrical conductivity of the PVA hydrogels are significantly improved. The LDH and nanocellulose uniformly dispersed in the mixed solvent play a vital role in regulating the hydrogen bond network structure during the PVA precipitation process, thereby improving the cross-linking uniformity of the hydrogel network and promoting the construction of a multi-layer porous structure.

[0029] 2. Compared with pure PVA hydrogel, the mechanical properties of the PVA composite hydrogel prepared in this application are improved in terms of strength and toughness. In addition, the rich porous network in the hydrogel provides an ion transport pathway. The conductivity of the PVA composite hydrogel reaches 1.16S / m, showing a stable resistance change under repeated deformation, and maintaining high conductivity even at a low temperature of -20°C. Therefore, this application has practical significance for promoting the application of PVA-based conductive ion hydrogels in biosensing materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0031] Figure 1 (a) is a schematic diagram of the connection bonds between different components in the LCP composite hydrogel in Example 1, Figure 1 (b) is the pure PVA hydrogel prepared by repeated freeze-thaw method in Comparative Example 4, Figure 1 (c) is a three-dimensional network structure diagram of pure PVA hydrogel prepared by freezing and salting out method through Hofmeister effect in comparative example 1, Figure 1 (d) is a three-dimensional network structure diagram of the LP composite hydrogel prepared in Comparative Example 3. Figure 1 (e) is a three-dimensional network structure diagram of the LCP composite hydrogel prepared by the freezing salting-out method in Example 1;

[0032] Figure 2 (a) is the tensile strength of the hydrogels of Examples 1-3 and Comparative Examples 1-9, Figure 2 (b) is the elongation at break of the hydrogels of Examples 1-3 and Comparative Examples 1-9, Figure 2 (c) is the elastic modulus of the hydrogels of Examples 1-3 and Comparative Examples 1-9, Figure 2 (d) is the toughness of the hydrogels of Examples 1-3 and Comparative Examples 1-9;

[0033] Figure 3 (a) is the conductivity of the hydrogels of Examples 1-3 and Comparative Example 1, Figure 3 (b) is the FTIR spectra of the hydrogels of Comparative Example 1, Comparative Example 3 and Example 1, Figure 3 (c) is the XRD spectrum of the hydrogels of Comparative Example 1, Comparative Example 3 and Example 1, Figure 3 (d) is the crystallinity of PVA in the hydrogels of Comparative Example 1, Comparative Example 3 and Example 1;

[0034] Figure 4 (a) is the SEM image of the hydrogel of Comparative Example 1, Figure 4 (b) is a SEM image of the hydrogel of Example 1, which has EDX spectra of C, O, Mg and Al. Figure 4 (c) is the expansion ratio of the hydrogel in Example 1 and Comparative Examples 1-2 after washing with distilled water, Figure 4 (d) is the volume change of the hydrogels in Comparative Example 1, Comparative Example 3 and Example 1 during oven drying;

[0035] Figure 5 (a) is the stress of the LCP composite hydrogel in Example 1 when cyclically stretched under different strains, Figure 5 (b) is the stress of the LCP composite hydrogel in Example 1 during cyclic compression at 50% compressive strain, Figure 5 (c) is the mechanical comparison with other PVA hydrogels. Figure 5 (d) is a photo of LCP composite hydrogels prepared using molds of different shapes;

[0036] Figure 6 (a) shows the change in relative resistance and strain coefficient of the LCP composite hydrogel in Example 1 as the tensile strain increases. Figure 6 (b) is the relative resistance change of the LCP composite hydrogel in Example 1 under different tensile strains over time, Figure 6 (c) is the relative resistance change of the LCP composite hydrogel in Example 1 under different pressures over time, Figure 6 (d) is the relative resistance change of the LCP composite hydrogel in Example 1 under a cyclic compression release test lasting 100 cycles, Figure 6 (e) is a photograph of the LCP composite hydrogel in Example 1 emitting light through a light bulb at room temperature and -20°C. Figure 6(f) Electrical comparison with other PVA hydrogels;

[0037] Figure 7 is the change of tensile strength and elongation at break of LCP composite hydrogel after different pre-stretching in Example 1;

[0038] Figure 8 (a) shows the change in tensile strength of the LCP composite hydrogel in Example 1 and Examples 4-6 after salting out in Na2SO4 salt solution of different concentrations, and 8 (b) shows the change in tensile strength of the LCP composite hydrogel in Example 1 and Examples 7-9 after salting out in Na2SO4 salt solution for different times. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0040] Unless otherwise specified, the experimental methods used in the examples of this application are all conventional methods.

[0041] In the following examples and comparative examples, unless otherwise specified, all raw materials can be obtained by commercial purchase or conventional methods.

[0042] Eucalyptus cellulose was supplied by Asia Symbol (Shandong) Pulp and Paper Co., Ltd. PVA with a Mw of 145,000, sodium bromide (NaBr), sodium sulfate (Na2SO4), hydrochloric acid (HCl), sodium hypochlorite (NaClO), sodium hydroxide (NaOH), TEMPO and LDH [Mg6Al2(CO3)(OH) 16 ·4H2O] was purchased from Macklin Co., Ltd.

[0043] Example 1

[0044] The method for preparing the strong and conductive hydrotalcite / nanocellulose / PVA composite hydrogel based on the Hofmeister effect in this embodiment comprises the following steps:

[0045] (1) 0.4 g NaBr and 0.064 g TEMPO were dissolved in 400 mL deionized water, followed by the addition of 4 g cellulose pulp, and 10 mL of a 24 mmol NaClO solution was gradually added dropwise to the mixture to initiate oxidation. During the oxidation process, the pH value of the mixture was continuously monitored and maintained at 10 by the addition of a 0.5 M NaOH solution. When the pH value of the mixture decreased by less than 0.05 per hour, 2 mL of ethanol was added to quench the oxidation. The pH of the mixture was adjusted to neutral by the addition of a 0.5 M HCl solution, and the mixture was centrifuged repeatedly at 10,000 rpm for 6 minutes. The precipitate was washed with distilled water to obtain oxidized cellulose, and the oxidized cellulose was then dispersed in distilled water to 0.2 wt %, and ultrasonically treated at a power of 1300 w for 10 minutes and stored in a refrigerator for later use.

[0046] (2) LDH nanosheets were prepared by ultrasonically treating LDH aqueous solution at a power of 1300 W for 20 min.

[0047] (3) The PVA solution is prepared by dissolving PVA in water at 100°C.

[0048] (4) Then, the LDH nanosheets and nanocellulose dispersion were mixed with the PVA solution by stirring and ultrasonic treatment. The concentrations of nanocellulose, LDH and PVA in the mixture were 1.0 wt%, 1.2 wt% and 8 wt%, respectively. In the freezing salting-out process, the mixture was immersed in a 1.5 M Na2SO4 solution for salting-out for 24 hours to promote the formation of the shape, and the hydrotalcite / nanocellulose / PVA composite hydrogel was prepared, which was recorded as LCP composite hydrogel.

[0049] Example 2

[0050] The hydrotalcite / nanocellulose / PVA composite hydrogel provided in this embodiment can refer to Example 1, except that the added amounts of hydrotalcite / cellulose are 1.2 wt % and 0.6 wt %, respectively.

[0051] Example 3

[0052] The hydrotalcite / nanocellulose / PVA composite hydrogel provided in this embodiment can refer to Example 2, except that the added amounts of hydrotalcite / cellulose are 1.2 wt % and 1.2 wt %, respectively.

[0053] Example 4

[0054] The hydrotalcite / nanocellulose / PVA composite hydrogel provided in this embodiment can refer to Example 1, except that the mixture is immersed in a Na2SO4 solution with a concentration of 0.5M.

[0055] Example 5

[0056] The hydrotalcite / nanocellulose / PVA composite hydrogel provided in this embodiment can refer to Example 1, except that the mixture is immersed in a Na2SO4 solution with a concentration of 1.0 M.

[0057] Example 6

[0058] The hydrotalcite / nanocellulose / PVA composite hydrogel provided in this embodiment can refer to Example 1, except that the mixture is immersed in a Na2SO4 solution with a concentration of 2.0M.

[0059] Example 7

[0060] The hydrotalcite / nanocellulose / PVA composite hydrogel provided in this embodiment can refer to Example 1, except that the mixture is immersed in a 1.5M Na2SO4 solution for 6 hours.

[0061] Example 8

[0062] The hydrotalcite / nanocellulose / PVA composite hydrogel provided in this embodiment can refer to Example 1, except that the mixture is immersed in a 1.5M Na2SO4 solution for 12 hours.

[0063] Example 9

[0064] The hydrotalcite / nanocellulose / PVA composite hydrogel provided in this embodiment can refer to Example 1, except that the mixture is immersed in a 1.5M Na2SO4 solution for 36 hours.

[0065] Comparative Example 1

[0066] The pure PVA hydrogel provided in this comparative example can refer to Example 1, except that the addition amount of cellulose / hydrotalcite is 0wt% / 0wt% (freezing salting out method).

[0067] Comparative Example 2

[0068] The PVA / LDH composite hydrogel provided in this comparative example can refer to Example 1, except that the amount of hydrotalcite added is 0.6 wt % and the amount of cellulose added is 0 wt % (freezing salting out method).

[0069] Comparative Example 3

[0070] The PVA / nanocellulose composite hydrogel provided in this comparative example can refer to Example 1, except that the amount of hydrotalcite added is 1.2 wt % and the amount of cellulose added is 0 wt % (freezing salting out method).

[0071] Comparative Example 4

[0072] The PVA / LDH composite hydrogel provided in this comparative example can refer to Example 1, except that the addition amount of cellulose / hydrotalcite is 0wt% / 0wt%, and a repeated freeze-thaw method is used (the freezing salting-out treatment step is replaced by repeated freeze-thaw treatment: during the freeze-thaw process, the composite mixture is poured into a mold and frozen at -20°C for 10 hours, and then thawed at room temperature for 10 hours, and the freezing and thawing are repeated 5 times each).

[0073] Comparative Example 5

[0074] The PVA / LDH composite hydrogel provided in this comparative example can refer to Example 1, except that the amount of hydrotalcite added is 0.6wt%, and a repeated freeze-thaw method is used (the freezing salting-out treatment step is replaced by repeated freeze-thaw treatment: during the freeze-thaw process, the composite mixture is poured into a mold and frozen at -20°C for 10 hours, then thawed at room temperature for 10 hours, and the freezing and thawing are repeated 5 times each).

[0075] Comparative Example 6

[0076] The PVA / LDH composite hydrogel provided in this comparative example can refer to Example 1, except that the hydrotalcite addition amount is 1.2 wt% and the repeated freeze-thaw method is used (the freezing salting-out treatment step is replaced by repeated freeze-thaw treatment: during the freeze-thaw process, the composite mixture is poured into a mold and frozen at -20°C for 10 hours, and then thawed at room temperature for 10 hours, and the freezing and thawing are repeated 5 times each).

[0077] Comparative Example 7

[0078] The PVA / LDH composite hydrogel provided in this comparative example can refer to Example 1, except that the added amounts of hydrotalcite / cellulose are 1.2wt% and 0.6wt%, respectively, and a repeated freeze-thaw method is used (the freezing salting-out treatment step is replaced by repeated freeze-thaw treatment: during the freeze-thaw process, the composite mixture is poured into a mold and frozen at -20°C for 10 hours, then thawed at room temperature for 10 hours, and the freezing and thawing are repeated 5 times each).

[0079] Comparative Example 8

[0080] The PVA / LDH composite hydrogel provided in this comparative example can refer to Example 1, except that the added amounts of hydrotalcite / cellulose are 1.2wt% and 1.0wt%, respectively, and a repeated freeze-thaw method is used (the freezing salting-out treatment step is replaced by repeated freeze-thaw treatment: during the freeze-thaw process, the composite mixture is poured into a mold and frozen at -20°C for 10 hours, then thawed at room temperature for 10 hours, and the freezing and thawing are repeated 5 times each).

[0081] Comparative Example 9

[0082] The PVA / LDH composite hydrogel provided in this comparative example can refer to Example 1, except that the added amounts of hydrotalcite / cellulose are 1.2 wt% and 1.2 wt% respectively, and the repeated freeze-thaw method is adopted (the freezing salting-out treatment step is replaced by repeated freeze-thaw treatment: during the freeze-thaw process, the composite mixture is poured into a mold and frozen at -20°C for 10 hours, and then thawed at room temperature for 10 hours, and the freezing and thawing are repeated 5 times each).

[0083] Test example

[0084] Using Spectrum 3 Tri-Range MIR / NIR / FIR spectrometer at 5500-650cm -1 Fourier transform infrared spectra (FTIR) of different PVA hydrogels were measured in ATR mode within a range of 1000 nm. The XRD patterns of different PVA hydrogels were analyzed by Cu-targeted Kα X-rays in the 2θ scanning range between 5° and 75° using an Advance D8 X-ray powder diffractometer. The crystallinity was obtained by analyzing the XRD patterns of the hydrogels by the integrated ratio of the crystallization peak area. The images of the internal network structure and element distribution of the PVA hydrogels were measured at 10 kV by SEM (Sigma 500) equipped with an energy dispersive spectrometer (EDS). The mechanical properties of different PVA hydrogels were measured by tension and compression using an electronic universal / tensile tester (Shimadzu AGS-X). The samples used in the test were dumbbell-shaped hydrogels with a rectangular size of approximately 15 mm × 12 mm at both ends and a rectangular size of 30 mm × 4 mm in length in the center. The conductivity of different PVA hydrogels was evaluated using a circuit with hydrogels, a 3-volt battery, and a light-emitting diode. The impedance of the LCP was measured by connecting the cylindrical hydrogel to an electrochemical workstation using two copper U-clip leads. The conductivity of the hydrogel was calculated by the following equation:

[0085] σ=dAR

[0086] Where σ is the conductivity, d is the thickness of the hydrogel, A is the cross-sectional area of ​​the hydrogel, and R is the impedance of the hydrogel.

[0087] (1) During the TEMPO oxidation process, the primary hydroxyl groups of cellulose molecules are selectively converted into carboxyl groups. Based on the electrostatic repulsion between carboxyl groups, with the help of ultrasonic treatment, oxidized cellulose dissociates into high aspect ratio nanofibers in the aqueous phase. Under mechanical stirring, nanocellulose can be uniformly mixed with LDH nanosheets and PVA in an aqueous environment.

[0088] During the gelation process, hydrogen bonds are formed between PVA molecules and nanocellulose. Al-OC bonds are formed between LDH nanosheets and the hydroxyl groups in PVA and nanocellulose. Figure 1(a)). The LCP composite hydrogel forms a dense three-dimensional network structure based on rich and high-density cross-linking. During the traditional repeated freeze-thaw treatment, ice crystals form and squeeze the dissolved PVA molecular chains to form a PVA-rich phase, and the tightly packed PVA molecular chains form hydrogen bonds and crystals ( Figure 1 (b)). Using the freezing salting-out treatment, the PVA molecules squeezed out by the ice crystals will further precipitate and aggregate in the high-concentration salt solution, thus forming a tighter connection and significantly improving the crystallinity ( Figure 1 (c)). After adding LDH, the enrichment and precipitation of PVA tend to use LDH nanosheets as attachment sites and form a higher density crystal structure around them ( Figure 1 (d)). Further addition of strip-shaped nanocellulose is more conducive to the formation of a dense network structure and crystallization in PVA molecules ( Figure 1 (e)). With the increase of cross-linking density within the hydrogel network and the improvement of PVA crystallinity, this LCP composite hydrogel has good elasticity and toughness. In addition, the optimization of ion transport channels and the assistance of nanocellulose and LDH nanosheets are expected to improve the conductivity and sensitivity of the hydrogel.

[0089] During the freezing salting out process, the concentration and immersion time of the Na2SO4 solution significantly affected the microstructure of the hydrogel. As the concentration of Na2SO4 increased from 0.5M to 2.0M, the tensile strength of the hydrogel increased at 1.5M and then decreased ( Figure 8 a). When the optimal concentration of Na2SO4 solution was used for salting out, the tensile strength of the hydrogel increased steadily within 24 h ( Figure 8 b). However, too long an immersion time may destroy the microstructure within the hydrogel network, resulting in a decrease in tensile strength. Based on the above data, the subsequent salting-out process of the frozen samples was performed by immersing them in a 1.5 M sodium sulfate solution for 24 h.

[0090] (2) Ice crystals compress the PVA molecular chains, aggregate and crystallize during the freezing and salting out process. The PVA solution is converted into a stable hydrogel and exhibits tensile resistance based on the improvement of structural order and the establishment of network structure. During the freezing and salting out process, the Hofmeister effect occurs. When PVA is immersed in a high concentration of Na2SO4 solution, the hydrophilic anion SO4 2- The hydrophilic polymer chains are aggregated by salting out, and new hydrogen bonds are formed between the hydroxyl groups of the PVA molecules, which promotes their crystallization and makes the network structure more dense and stable. Figure 2(a) shows the tensile strength of PVA hydrogels prepared by repeated freeze-thaw and freeze-salting out methods with different additions of LDH and nanocellulose. By adding LDH nanosheets, PVA molecules aggregate and arrange in an orderly manner during the freeze-salting out process, using the uniformly dispersed layered LDH structure as a template to form a more uniform hydrogen bond network and a more stable hydrogel structure. Well-dispersed LDH nanosheets can act as stress transfer and dissipation centers, reduce stress concentration caused by segment breakage, and prevent crack propagation and structural damage. With the addition of LDH nanosheets, the tensile strength of LP composite hydrogels gradually increased, and the LP composite hydrogels prepared by repeated freeze-thaw and freeze-salting out processes increased from 0.6MPa to 0.65MPa and from 2.08MPa to 4.02MPa, respectively. On the basis of adding 1.2% LDH nanosheets, the addition of nanocellulose can further improve the tensile strength of LCP composite hydrogels. When the addition amount of nanocellulose is 1.0%, the LCP composite hydrogel prepared by freeze-salting out shows the highest tensile strength, reaching 5.03MPa. Adding excessive amounts of nanocellulose reduced the tensile strength of the composite gel.

[0091] With the improvement of the uniformity of hydrogen bonding, the entanglement between PVA and nanocellulose in the composite hydrogel and its connection with LDH nanosheets effectively reduced the stress concentration caused by structural defects during stretching. The orderly breaking of hydrogen bonds in the multilayer network structure gradually dissipated the energy and significantly improved the elongation at break ( Figure 2 (b)). At the same time, the elastic modulus and toughness of the hydrogel showed similar change trends with the increase of LDH nanosheets and nanocellulose content ( Figure 2 (cd)). In the LCP composite hydrogel, PVA molecules are anchored on the surface of LDH nanosheets and nanocellulose to form a more uniform network structure. During the stretching process, the uniformly dispersed rigid LDH nanosheets and nanocellulose help to disperse the stress of PVA, so that the LCP composite hydrogel has high mechanical strength. At the same time, under large-scale deformation, when part of the stress concentration area breaks, the stress will be redistributed to other areas. With the staged fracture of the network structure, the toughness of the composite hydrogel is greatly improved. The mechanical properties of the hydrogel prepared by the freeze-salting method are better than those prepared by the repeated freeze-thaw method. The addition of LDH and nanocellulose has comprehensively improved the strength and toughness of the composite hydrogel.

[0092] (3) The properties of the internal network structure of the hydrogel will affect its electrical conductivity. With the addition of LDH and nanocellulose, the pore structure in the hydrogel will change significantly, thereby changing the ion transport path. The conductivity of the composite hydrogel prepared by the freeze-salting process also reached a maximum value of 1.16 S / m. The hydrogel contained 1.2 wt% LDH nanosheets and 1.0 wt% nanocellulose ( Figure 3(a)). Adding more nanocellulose will have a negative impact on the conductivity of the hydrogel with too high a crosslinking density. Therefore, in this application, the amount of nanocellulose was set to 1.0 wt% for the subsequent preparation of the composite hydrogel material.

[0093] The freezing and salting-out treatment had no significant effect on the chemical structure of PVA. -1 、1418cm -1 and 2915cm -1 The absorption peaks corresponding to the stretching vibrations of CC, -CH- and -CH2- are shown at Figure 3 (b)). After adding LDH nanosheets and nanocellulose, the composite hydrogel -1 、1062cm -1 and 893cm -1 The characteristic absorption peaks at 1420 cm-1 are attributed to the CH, CO and -COC groups of cellulose. -1 The absorption peak corresponds to CO3 in LDH 2- TEMPO oxidation selectively introduces carboxyl groups into nanocellulose, resulting in the absorption peak of carboxyl groups in the composite hydrogel at 1750 cm -1 845cm -1 The new characteristic peaks at 3360 cm-1 indicated that Al-OC bonds were formed between LDH nanosheets and nanocellulose. The -OH stretching vibration peaks of PVA and LDH were initially located at 3360 cm-1, -1 and 3448cm -1 Around 3250 cm -1 , indicating the formation of hydrogen bonds and the enhancement of interactions between nanocelluloses.

[0094] The freezing and salting out process can enhance the aggregation of PVA molecules by compressing them at the microscale, thereby promoting their crystallization. After gelation, pure PVA hydrogel showed obvious crystal structure diffraction peak characteristics at 20.2° and 22.3° ( Figure 3 (c)). The composite hydrogel shows characteristic peaks of cellulose crystallization at 14°, 22° and 35°, and characteristic peaks of LDH at 11.3° and 34.5°. It can be seen that the mixing and freezing salting-out process has no significant effect on the crystal structure of nanocellulose and LDH.

[0095] The crystallinity of PVA significantly affects the mechanical properties of its hydrogel material. Due to compression, the PVA molecular chains are more likely to form a directional arrangement during the freezing and salting out process, thus forming an ordered crystal structure. The crystallinity of the PVA hydrogel material prepared by the freezing and salting out method reached 4.31% ( Figure 3(d)). During the freeze-salting process of the composite system, the lamellar LDH nanosheets and fibrous nanocellulose provided binding and aggregation sites for the precipitated PVA. PVA prefers to be oriented based on the network structure of nanocellulose and LDH nanosheets. In the composite hydrogel, the crystallinity of PVA increased to 10.05%.

[0096] (4) After freeze drying, the PVA hydrogel sample can be converted into aerogel, so that the internal structure can be observed using SEM. After the freezing and salting out process, the pure PVA molecules self-aggregate to form a clear three-dimensional network structure. The network skeleton is composed of coarse fibers cross-linked by PVA molecules, and the internal pore size exceeds 10 μm ( Figure 4 (a)). With the addition of LDH and nanocellulose, the network structure inside the hydrogel becomes more complex, forming a multi-level pore structure. There is a denser network connection structure in the pores with a diameter of 1-5 μm ( Figure 4 (b)). The addition of LDH nanosheets and nanocellulose effectively improved the cross-linking degree and uniformity between the components. According to the EDS graph, the elements C, O, Mg, and Al in the composite hydrogel are evenly distributed, indicating that the three components are evenly dispersed.

[0097] When the prepared PVA hydrogel was repeatedly soaked and washed with deionized water, as the salt ions were washed away, some loosely connected areas broke hydrogen bonds due to enhanced hydration, causing the hydrogel volume to expand. The swelling rate of pure PVA hydrogel in water was 119% ( Figure 4 (c)). The more uniform hydrogen bonding and the strong structure reduced the swelling ratio of the LCP composite hydrogel to 103%. When the hydrogel was dried in an oven, the hydration layer on the surface of the components disappeared as the water evaporated, and hydrogen bonds were formed between the three components, causing the hydrogel to shrink. The volume of the pure PVA hydrogel shrank to 12.39% of its original volume ( Figure 4 (d)). Due to the optimization of the hydrogel pore network and the improvement of the stability of the skeleton structure, the dry volumes of the composite hydrogels with the addition of LDH, LDH and nanocellulose reached 15.73% and 19.47% of their original volumes, respectively.

[0098] (5) When 100 stretching cycles were performed at 200% and 400% elongation at a speed of 30 mm / min, Figure 5 As shown in (a), the composite hydrogel maintains its shape during the cycle. The high overlap of the stretching hysteresis loops indicates that the stretching process does not cause significant irreversible damage to the internal structure of the hydrogel. After the stretching cycle, the stress loss of the composite hydrogel at 200% and 400% elongation was 10.2% and 13.37%, respectively, compared with the original sample. The rich and dense cross-linked network within the hydrogel maintains its strength and structural integrity during repeated stretching and contraction, enhancing its stability and service life.

[0099] Under tensile stress, some hydrogen bonds within the hydrogel break, the PVA molecular chains and strip-shaped nanocellulose are aligned along the stretching direction, and the layered LDH nanosheets are deflected. When the composite hydrogel is kept in a stretched state for a period of time, the spatial distance between the aligned PVA and nanocellulose is relatively reduced due to the reduction in width along the stretching direction during the stretching process, allowing new hydrogen bonds to form between the three components of the hydrogel, further improving its mechanical properties. When the hydrogel is stretched to 200%, its tensile strength reaches 7.12MPa, an increase of 40%, and the elongation at break also increases to 105% ( Figure 7 ). When the stretching ratio increases to 400%, the tensile strength and elongation at break of the hydrogel reach 7.53MPa and 1209%, respectively. However, further increasing the stretching ratio to 600% may cause damage to the structure of the hydrogel, resulting in a decrease in its mechanical properties.

[0100] At the same time, the LCP composite hydrogel exhibited excellent compression properties. When the compression ratio was 50%, the compressive stress was 468 kPa ( Figure 5 (b) During compression, the pore structure within the hydrogel deforms, but the cross-linking sites formed by the components do not rupture on a large scale. During repeated compression cycles, the compressive stress of the hydrogel gradually decreases, decreasing by 19.5% after 50 cycles.

[0101] Compared with the mechanical properties of PVA gel in the prior art, the LCP composite hydrogel prepared in this application has higher strength, toughness and recyclability ( Figure 5 (c)). Based on the simple preparation process and excellent mechanical properties, it is very convenient to use the corresponding mold to prepare LCP composite hydrogels of various shapes ( Figure 5 (d)). Spherical hydrogels can be used for table tennis training.

[0102] (6) PVA hydrogel exhibits electrical conductivity based on the dissociated Na2SO4 ions in water, and the rich pore structure of the hydrogel acts as an electron transport channel. Based on the huge surface area of ​​the multilayer porous structure of the hydrogel, the carboxyl groups on the surface of nanocellulose can attract Na + , and provide more jumping sites for ion transfer, thereby improving ionic conductivity. At the same time, the spatial gaps between LDH nanosheets can provide fast ion transport channels. Therefore, when LDH nanosheets and nanocellulose are added, the ionic conductivity of the composite hydrogel reaches 1.16S / m. Changes in the internal network structure of the LCP composite hydrogel will affect ion transport, resulting in changes in the conductivity of the hydrogel. During the stretching process, the conductive path within the hydrogel becomes longer and narrower, and the three components deflect or change direction along the stretching direction, resulting in significant deformation of the spatial channels within the three-dimensional network structure. Figure 6As shown in (a), the resistance of the composite hydrogel increases with the increase of tensile strain. The sensitivity coefficient (strain factor) of the LCP composite hydrogel was further analyzed. When the elongation is lower than 150%, the strain factor of the hydrogel is at a high level, but shows a linear downward trend, indicating that the conductivity sensitivity decreases. As the hydrogel is further stretched, the strain factor remains at around 0.8, which is a quantifiable range for evaluating the conductivity elongation. When the hydrogel is repeatedly stretched in the range of 50% to 400% in a short period of time, the resistance of the composite hydrogel maintains a stable rate of change at the same elongation ( Figure 6 (b)).

[0103] Under a specific compressive stress, the thickness of the hydrogel decreases and the surface area increases, resulting in a decrease in the resistance of the hydrogel. When the compressive stress is 2.5 kPa, the relative resistance of the LCP composite hydrogel changes by about 10% and remains stable when the stress is stable ( Figure 6 (c)). As the stress gradually increases, the relative resistance change of the hydrogel gradually decreases. Under a compressive stress of 30 kPa, the resistance of the hydrogel decreases to 20% of its original value, which means that the conductivity increases fourfold. During 100 rapid compression recovery cycles, the relative resistance change of the hydrogel shows excellent stability and high sensitivity ( Figure 6 (d)).

[0104] The electrical conductivity of ionic hydrogels decreases with decreasing temperature. The electrical conductivity of the composite hydrogels at low temperatures was evaluated. Figure 6 As shown in (e), the composite hydrogel still has good conductivity at -20°C, keeping the small light bulb bright. When the temperature drops from 20°C to -20°C, the conductivity of the composite hydrogel remains at a high level of 0.95S / m, a decrease of 17.64% ( Figure 6 (f)). Compared with other PVA hydrogels published in recent years at different temperatures, the performance of LCP composite hydrogel is better than most previously reported conductive PVA hydrogels, showing significant advantages. In conclusion, LCP composite hydrogel has stable and sensitive electrical signal transmission performance.

[0105] The present invention discloses an effective method for preparing tough PVA-based conductive ion hydrogels. By incorporating LDH nanosheets and nanocellulose into PVA solution and applying a freezing salting-out process, the mechanical properties and electrical conductivity of the PVA hydrogels are significantly improved. The LDH and nanocellulose uniformly dispersed in the mixed solvent play a vital role in regulating the hydrogen bond network structure during the PVA precipitation process, thereby improving the cross-linking uniformity of the hydrogel network and promoting the construction of a multilayer porous structure.

[0106] Compared with pure PVA hydrogel, the mechanical properties of PVA composite hydrogel are improved in terms of strength and toughness. In addition, the rich porous network within the hydrogel provides an ion transport pathway. The conductivity of the PVA composite hydrogel reaches 1.16S / m, showing a stable resistance change under repeated deformation, and maintaining high conductivity even at a low temperature of -20°C. Therefore, this application has practical significance for promoting the application of PVA-based conductive ion hydrogels in biosensing materials.

[0107] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing a strong and conductive hydrotalcite / nanocellulose / PVA composite hydrogel based on the Hofmeister effect, characterized in that: The following steps are involved: The hydrotalcite nanosheets, nanocellulose dispersion and PVA solution are mixed, stirred and subjected to ultrasonic treatment to obtain a composite mixture; the composite mixture is subjected to freeze-salting-out treatment to obtain a hydrotalcite / nanocellulose / PVA composite hydrogel.

2. The method for preparing a strong and conductive hydrotalcite / nanocellulose / PVA composite hydrogel based on the Hofmeister effect according to claim 1, characterized in that: The specific process of freezing salting out is: The hydrotalcite / nanocellulose / PVA composite hydrogel was immersed in a Na2SO4 solution with a concentration of 0.5-2.0 M for salting out for 6-36 hours to promote shape formation.

3. The method for preparing the tough and conductive hydrotalcite / nanocellulose / PVA composite hydrogel based on the Hofmeister effect according to claim 1, characterized in that: The preparation process of nanocellulose dispersion is as follows: NaBr and TEMPO were dissolved in deionized water, and then cellulose pulp was added. NaClO solution was gradually added dropwise to the mixture to start oxidation. During the oxidation process, the pH value of the mixture was continuously monitored and maintained at 9.8-11.5 by adding NaOH solution dropwise. When the pH value of the mixture decreased by less than 0.05 per hour, ethanol was added to quench the oxidation. The pH of the mixture was adjusted to neutral by adding HCl solution. Centrifugation was repeated at 10000 rpm for 6 minutes. The precipitate was washed with distilled water to obtain oxidized cellulose. The oxidized cellulose was then dispersed in distilled water to 0.2 wt %, and ultrasonically treated at a power of 1300 w for 10 minutes and stored in a refrigerator for use.

4. The method for preparing a strong and conductive hydrotalcite / nanocellulose / PVA composite hydrogel based on the Hofmeister effect according to claim 3, characterized in that: The dosage ratio of NaBr, TEMPO, deionized water, cellulose pulp and NaClO is 0.4 g:0.064 g:400 mL:4 g:10 mL.

5. The method for preparing the tough and conductive hydrotalcite / nanocellulose / PVA composite hydrogel based on the Hofmeister effect according to claim 3, characterized in that: The concentration of NaOH solution is 0.5M, and the concentration of HCl solution is 0.5M.

6. The method for preparing a strong and conductive hydrotalcite / nanocellulose / PVA composite hydrogel based on the Hofmeister effect according to claim 1, characterized in that: The preparation process of hydrotalcite nanosheets is as follows: The hydrotalcite aqueous solution was ultrasonically treated at a power of 1300 W for 20 minutes to obtain hydrotalcite nanosheets.

7. The method for preparing a strong and conductive hydrotalcite / nanocellulose / PVA composite hydrogel based on the Hofmeister effect according to claim 1, characterized in that: The preparation process of PVA solution is: PVA solution was prepared by dissolving PVA in water at 100°C.

8. The method for preparing a strong and conductive hydrotalcite / nanocellulose / PVA composite hydrogel based on the Hofmeister effect according to claim 1, characterized in that: The concentrations of nanocellulose, hydrotalcite and PVA in the hydrotalcite / nanocellulose / PVA composite hydrogel are 0.6-1.2wt%, 1.2wt% and 8wt%, respectively.

9. A tough and conductive hydrotalcite / nanocellulose / PVA composite hydrogel based on the Hofmeister effect, prepared according to the preparation method of any one of claims 1 to 8.

10. Use of the tough and conductive hydrotalcite / nanocellulose / PVA composite hydrogel constructed based on the Hofmeister effect according to claim 9 in the preparation of a flexible strain sensor.

Citation Information

Cited By

  • PVA / CNF water photovoltaic power generation composite material with bionic wood structure as well as preparation method and application of PVA / CNF water photovoltaic power generation composite material

    CN122381419A

  • A PVA / CNF water-vapor-driven power generation composite material of a biomimetic wood structure, a preparation method and application thereof

    CN122381419B